Influence of body mass index on outcome of the mechanically ventilated patients. Issue 1 (27th October 2010) - Anzueto, A; Frutos-Vivar, F; Esteban, A; Bensalami, N; Marks, D; Raymondos, K; Apezteguía, C; Arabi, Y; Hurtado, J; González, M; Tomicic, V; Abroug, F; et al.
Abstract : Background: There are limited data on the impact of body mass index on outcomes in mechanically ventilated patients. Methods: Secondary analysis of a cohort including 4698 patients mechanically ventilated. Patients were screened daily for management of mechanical ventilation, complications (acute respiratory distress syndrome, sepsis, ventilator associated pneumonia, barotrauma), organ failure (cardiovascular, respiratory, renal, hepatic, haematological) and mortality in the intensive care unit. To estimate the impact of body mass index on acute respiratory distress syndrome and mortality, the authors constructed models using generalised estimating equations (GEE). Results: Patients were evaluated based on their body mass index: 184 patients (3.7%) were underweight, 1995 patients (40%) normal weight, 1781 patients (35.8%) overweight, 792 patients (15.9%) obese and 216 patients (4.3%) severely obese. Severely obese patients were more likely to receive low tidal volume based on actual body weight but high volumes based on predicted body weight. In obese patients, the authors observed a higher incidence of acute respiratory distress syndrome and acute renal failure. After adjustment, the body mass index was significantly associated with the development of acute respiratory distress syndrome: compared with normal weight; OR 1.69 (95% CI 1.07 to 2.69) for obese and OR 2.38 (95% CI 1.15 to 4.89) for severely obese. There were no differences in outcomes (duration of mechanical ventilation, length of stay and mortality in intensive care unit and hospital) based on body mass index categories. Conclusions: In this cohort, obese patients were more likely to have significant complications but there were no associations with increased mortality.